EFFECT OF INTENSIVE REGENERATION PRUNING OF FROSTBITTEN PEACH TREES ‘HARBINGER’ CV. ON THEIR GROWTH AND YIELDING - Bożena Radajewska; Michał Szklarz (Acta Scientiarum Polonorum: Hortorum Cultus, 2008)
Studies were carried out in the years 2006–2008 in Przybroda near Poznań. Objects of studies consisted of 8-year old peach trees ‘Harbinger’ cultivar grown on three rootstocks: Manchurian Peach, Sand Cherry and Rakoniewicka Seedling. Tree crowns had a vase form and they were strongly damaged by frost during the winter 2005/2006. In spring 2006, intensive tree pruning was carried out. The objective of the studies was the estimation of the effect of a radical pruning of frostbitten trees on their regeneration and yielding, as well as to estimate the role of rootstocks in this process. Studies have shown that the tree pruning evoked a very strong compensation growth, the reaction of trees was the stronger, the more intensive was the tree pruning. As a result of the pruning, after 3 years, the lowered tree height (on the average by 40–50 cm) was maintained in relation to the control trees. After pruning, in the tree crown, longer productive long-shoots with diameters > 0.5 cm, developed as compared with the control. However, the radical pruning of trees caused in the third year after pruning a decrease in tree yielding from 30 to 40%, in comparison with the not pruned trees.